Selection of grain sorghum lines efficient and responsive to phosphorus application - Rodrigues, Fabricio; Magalhães, Jurandir Vieira de; Guimarães, Claudia Teixeira; Tardin, Flávio Dessaune; Schaffert, Robert Eugene (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to select sorghum lines simultaneously responsive to phosphorus fertilization and with high productive efficiency regarding this nutrient. Thirty six sorghum inbred lines were evaluated in a randomized complete block design, with two replicates. The traits used to evaluate the productive efficiency were average yield and efficiencies of absorption, utilization, and use of phosphorus, with and without phosphorus fertilization. For the analysis of the responsivity to the nutrient, the evaluated traits were relative yield and apparent recovery, physiological, and agronomic efficiencies. The lines were genetically divergent as to the efficiencies of absorption, utilization, and use of phosphorus, and to the responsivity to the nutrient, suggesting the possibility of producing hybrids destined to different market niches. The most responsive lines were P9401, BR007B, BR008B, SC414‑12E, and SC566, and the most efficient ones under low phosphorus availability were ATF40B, SC566, BR005R, CMSXS225, and BR012 (R6). The ATF40B, ATF54 (f61), ATF54 (f596), QL3, and SC566 lines showed better simultaneous performance for the different evaluated efficiencies and for the responsivity to phosphorus. The evaluation of productivity alone, under different phosphorus availabilities, already makes it possible to identify efficient and responsive lines to phosphorus.